"Why are so few women requesting attendance at protected persons' programmes?" : a thesis presented in partial fulfilment of the requirements for a degree of Master of Social Work (Applied), Massey University - Baxter, Brenda Eileen (Massey University, 1999)
The focus of this study is on the low number of requests made by women in order to attend domestic violence education programmes under section 29 (1) (a) of the Domestic Violence Act 1995. It examines the exchange of information between some Family Court clients and the associated Family Court practitioners when protection orders are obtained. This study acknowledges the low attendance at protected person' programmes and investigates how the information exchange fails to achieve greater numbers of participants on Family Court-funded programmes. The data is both qualitative and quantitative. The qualitative data comprises in-depth interviews with five protected persons and ten practitioners connected to the Family Court through their work with victims of domestic violence. The quantitative data is based upon a survey of twenty-two Family Court Coordinators. Both the interviews and the survey were designed to trace the processes used in exchanging significant information about the programmes, and to identify the successful methods of engaging more women in programmes. The study highlight the gap between the Family Court's provision of specialised services for abused women and the utilisation of those resources. The promotion of programmes has developed in an ad hoc manner which is reliant on the drive and commitment of key Family Court personnel. It is timely, three years after the introduction of the legislation, to examine why so few protected persons are requesting attendance at domestic violence programmes.
Keywords: Abused wives; New Zealand; Family violence prevention; Abused spouses